2016
DOI: 10.1016/j.jcz.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Insight into biting diversity to capture benthic prey in damselfishes (Pomacentridae)

Abstract: a b s t r a c tThe cerato-mandibular (c-md) ligament, joining the hyoid bar to the coronoid process of the angular, allows Pomacentridae to slam their mouth shut in a few milliseconds. Previous works have revealed that such a mechanism is used to feed, but some variability in biting patterns has been observed between two damselfish species. The pelagic feeder Amphiprion clarkii performs two different kinematic patterns to bite fixed prey, one that does not depend on the c-md ligament (biting-1) and one that do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…; Olivier et al . ) must possess specific gastric enzymes to be able to digest algae (Clements et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…; Olivier et al . ) must possess specific gastric enzymes to be able to digest algae (Clements et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…The Pomacentridae are a successful lineage of nearshore reef fishes (399 extant species; Eschmeyer and Fricke, 2016) that are one of the dominant vertebrate groups on coral reefs (Bellwood and Hughes, 2001;Allen, 1991;Bellwood et al, 2016). These fishes are highly amenable to this type of study because the evolution of their cranial morphology has tracked repeated transitions between benthic and pelagic feeding niches Frédérich et al, 2013;Olivier et al, 2016). Their value as an experimental system is further enhanced by the relative ease with which they may be captured in the wild or purchased through the aquarium trade, the readiness with which most damselfishes feed in aquaria and the amount of published information on their diets.…”
Section: Introductionmentioning
confidence: 99%
“…The cerato-mandibular (c-md) ligament, linking the ceratohyal bar of the hyoid apparatus with the coronoid processes of the lower jaw, is a pomacentrid synapomorphy (Olivier et al 2016a;Stiassny 1981). Previous kinematic studies revealed that this ligament allows rapid jaw closure (2 to 4 ms) which is used to produce sound and communicate (Colleye and Parmentier 2012;Parmentier et al 2007), to bite fixed prey (Olivier et al 2015(Olivier et al , 2016b or to graze on small filamentous algae (Olivier et al 2014). This ligament has been lost in several distantly related lineages, resulting in morphological modifications since species lacking this ligament have proportionally longer and thinner mandibles than species that have it (Frédérich et al 2014).…”
Section: Introductionmentioning
confidence: 99%